Identity Deconstruction and Humanity Ideology in Anis Chouchène’s Poem Untitled: A Riffaterre Semiotic Perspective - Mutmainah, Mia; Nafi’ah, Khotimatun; Binta, Silmi Malina; Ilham, Andri (Journal of Arabic Language Studies and Teaching, 2025)
This study examined Anis Chouchène's poem Untitled through Michael Riffaterre's semiotic theory, employing heuristic and hermeneutic readings. It aimed to explore how ungrammaticalities in the poem generated deeper meanings. At the heuristic level, the poem questions conventional Arab identity through irony and contradiction. The hermeneutic reading revealed a critique of moral and cultural decline in the Arab world, expressed through themes of disillusionment, hypocrisy, and the erosion of human values. The model of a nation that has eroded the value of humanity is reflected in the matrix of humanity, underscoring Chouchène's broader poetic message, particularly in Salām' Alaikum. The findings showed that Chouchène employed poetic language not only to challenge identity constructs but also to promote universal human values as essential foundations for justice and peace.